The Essence of Management Accounting - Buckley Adrian; Chadwick Leslie (Prentice Hall, 1991)
This book is concise, analytical and uniform in its approach to the key topics of good business practice. An invaluable reference source for managers on short course; for MBA and other students who wat to get quickly to the heart of the subject. Preface, An Introduction to Management Accounting, Materials, Labor, Absorption Costing, Marginal Costing and Breakeven Analysis, Absorption Costing V Marginal Costing, Budgeting and Budgetary Control, Standard Costing, Capital Investment Appraisal, Suggested Answers to Self Assessment Problems, Appendix 1: Present Value Tables and Annuity Tables, Index.